2018
DOI: 10.3389/fchem.2018.00057
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Drug Design in Epigenetics

Abstract: Epigenetic dysfunction has been widely implicated in several diseases especially cancers thus highlights the therapeutic potential for chemical interventions in this field. With rapid development of computational methodologies and high-performance computational resources, computer-aided drug design has emerged as a promising strategy to speed up epigenetic drug discovery. Herein, we make a brief overview of major computational methods reported in the literature including druggability prediction, virtual screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 229 publications
(226 reference statements)
0
39
0
Order By: Relevance
“…In contrast, in the absence of information on targets, LBDD relies on the knowledge of ligands that interact with a specific target, and these methods include ligand-based virtual screening (LBVS), similarity searching, quantitative structure-activity relationship (QSAR) modeling, and pharmacophore generation (Ferreira et al, 2015). Over the last years, a large number of studies have reported successful use of CADD in design and discovery of new drugs (Lu et al, 2018b). In this study we provide the comprehensive review of computational tools that led to discovery, design and optimization of KIs as anticancer drugs.…”
Section: In Silico Methods Used In Drug Designmentioning
confidence: 99%
“…In contrast, in the absence of information on targets, LBDD relies on the knowledge of ligands that interact with a specific target, and these methods include ligand-based virtual screening (LBVS), similarity searching, quantitative structure-activity relationship (QSAR) modeling, and pharmacophore generation (Ferreira et al, 2015). Over the last years, a large number of studies have reported successful use of CADD in design and discovery of new drugs (Lu et al, 2018b). In this study we provide the comprehensive review of computational tools that led to discovery, design and optimization of KIs as anticancer drugs.…”
Section: In Silico Methods Used In Drug Designmentioning
confidence: 99%
“…By using homology models of the DNMTs or, in theory, any of the epigenetic enzymes, it is possible to perform virtual screens of thousands of compounds at relatively little cost. As reviewed by Lu et al (2018), this approach has already led to the discovery of the DNMT inhibitors RG108, NSC14778, nanaomycin A, SET7 inhibitor DC_S100, and EZH2 inhibitor DCE_254, among others (Lu et al 2018). This approach could also be applied in toxicology to screen for potential epigenetic disruptors.…”
Section: Strategies For Toxico-epigenomic Screeningmentioning
confidence: 99%
“…[181][182][183] Due to inclusion of above said technologies in drug discovery campaigns, the current decade (2007-2017) has dragged prodigious progress globally in NSCLC pertaining to drug development and in clinical settings. [183][184][185][186][187] Novel targeted antineoplastic agents loaded with anticancer warhead to demonstrate imperious efficacy have been synthesized and introduced for clinical use. Second generation DAAPlouges including alectinib are known to be effective in greater than 50% NSCLC patients who were refractory to crizotinib.…”
Section: Conclusion and Future Prospectivesmentioning
confidence: 99%